Geostrategic interests of turkey and Iran in the Caspian region - Shukurov, Sabir I. (Linguistics and Culture Review, 2021)
The relevance of this article is due to the advantageous geostrategical position of the Republic of Azerbaijan in the Caspian region, which makes it a significant and attractive location for neighbouring states both politically and economically, causing not only partnership relations between the countries but also the probable insecurity of Azerbaijan's territorial integrity. The purpose of this study is to examine and analyze the complex of geostrategic relations in the Caspian region on the example of the relationship of the Republic of Azerbaijan with the Republic of Turkey and the Islamic Republic of Iran. The leading method for the study of this topic is, first of all, a deep and detailed analysis of the geostrategic and geopolitically advantageous position of the Republic of Azerbaijan, as well as the method of comparing its relations with neighbouring states, which makes it possible to imagine as accurately as possible the general geopolitical picture of the Caspian region.